A tumor mutational burden-derived immune computational framework selects sensitive immunotherapy/chemotherapy for lung adenocarcinoma populations with different prognoses - Zhang, Wenlong; Wei, Chuzhong; Huang, Fengyu; Huang, Wencheng; Xu, Xiaoxin; Zhu, Xiao (Frontiers in Oncology, 2023)
Background: Lung adenocarcinoma (LUAD) kills millions of people every year. Recently, FDA and researchers proved the significance of high tumor mutational burden (TMB) in the treatment of solid tumors. But no scholar has constructed a TMB-derived computing framework to select sensitive immunotherapy/chemotherapy for the LUAD population with different prognoses. Methods: The datasets were collected from TCGA, GTEx, and GEO. We constructed the TMB-derived immune lncRNA prognostic index (TILPI) computing framework based on TMB-related genes identified by weighted gene co-expression network analysis (WGCNA), oncogenes, and immune-related genes. Furthermore, we mapped the immune landscape based on 8 algorithms. We explored the immunotherapy sensitivity of different prognostic populations based on immunotherapy response, tumor immune dysfunction and exclusion (TIDE), and tumor inflammation signature (TIS) model. Furthermore, the molecular docking models were constructed for sensitive drugs identified by the pRRophetic package, oncopredict package, and connectivity map (CMap). Results: The TILPI computing framework was based on the expression of TMB-derived immune lncRNA signature (TILncSig), which consisted of AC091057.1, AC112721.1, AC114763.1, AC129492.1, LINC00592, and TARID. TILPI divided all LUAD patients into two populations with different prognoses. The random grouping verification, survival analysis, 3D PCA, and ROC curve (AUC=0.74) firmly proved the reliability of TILPI. The predictive ability of TILPI was associated with clinical characteristics including smoking and pathological stage. Furthermore, we estimated 3 types of immune cells threatening the survival of patients based on multiple algorithms. They were macrophage M0, T cell CD4 Th2, and T cell CD4 memory activated. Nevertheless, 5 immune cells including B cell, endothelial cell, eosinophil, mast cell, and T cell CD4 memory resting prolonged the survival. In addition, both the immunotherapy response and TIDE model proved the sensitivity of the low-TILPI population to immunotherapy. We also identified 7 intersected drugs for the LUAD population with poor prognosis, which included docetaxel, gemcitabine, paclitaxel, palbociclib, pyrimethamine, thapsigargin, and vinorelbine. Their molecular docking models and best binding energy were also constructed and calculated. Conclusions: We divided all LUAD patients into two populations with different prognoses. The good prognosis population was sensitive to immunotherapy while the population with poor prognosis benefitted from 7 drugs.